Shikonin induces the apoptosis and pyroptosis of EGFR-T790M-mutant drug-resistant non-small cell lung cancer cells via the degradation of cyclooxygenase-2 - Shaoyi Cao; Huaqiu Li; Xiaoyan Ye; Xinxing Xing; Yonghuan Xie; Xiangfeng Zeng; Hongjiao Liu; Xing Zhong; Xinyi Yang; Wenxiu Xing; Cairong Zhu; Xiaoping Wu (European Journal of Medical Research)
Abstract Background The T790M mutation in the epidermal growth factor receptor (EGFR) gene is the primary cause of resistance to EGFR-tyrosine kinase inhibitor (TKI) therapy in non-small cell lung cancer (NSCLC) patients. Previous research demonstrated that certain traditional Chinese medicine (TCM) monomers exhibit anti-tumor effects against various malignancies. This study aims to investigate the potentials of shikonin screened from a TCM monomer library containing 1060 monomers in killing EGFR-T790M drug-resistant NSCLC cells and elucidate the underlying mechanisms. Methods MTT method was used to screen for the TCM monomers with significant killing effects on H1975 cells carrying the EGFR-T790M mutation. The influences of the identified monomer shikonin on cell growth were determined by the colony formation assay. Annexin-V/PI staining and JC-1 staining were applied to detect the effects of shikonin on cell apoptosis. The influences of shikonin on cell membrane integrity were detected by lactate dehydrogenase (LDH) release assay. Reactive oxygen species (ROS) generation was analyzed using DCFH-DA as probe. The mechanisms of shikonin affecting the stability of cyclooxygenase-2 (COX-2) were evaluated by using specific inhibitors for protein degradation pathways. Western blotting was performed to assess the effects of the alteration of COX-2 expression or enzymatic activity on the related signal pathways as well as the apoptotic and pyroptotic markers. Results Shikonin was identified as a potent cytotoxic compound against EGFR-T790M-mutant NSCLC cells. Shikonin induced cell apoptosis and pyroptosis by triggering the activation of the caspase cascade and cleavage of poly (ADP-ribose) polymerase and gasdermin E by elevating intracellular ROS levels. Further investigations revealed that shikonin induced the degradation of COX-2 via the proteasome pathway, thereby decreasing COX-2 protein level and enzymatic activity and subsequently inhibiting the downstream PDK1/Akt and Erk1/2 signaling pathways through the induction of ROS production. Notably, COX-2 overexpression attenuated shikonin-induced apoptosis and pyroptosis, whereas COX-2 inhibition with celecoxib enhanced the cytotoxic effects of shikonin. Conclusions Combination treatment with shikonin and COX-2 inhibitor may be a suitable therapeutic strategy for EGFR-T790M-mutant NSCLC treatment.